Clinical utility of noninvasive scores in assessing advanced hepatic fibrosis in patients with type 2 diabetes mellitus: a study in biopsy-proven non-alcoholic fatty liver disease - YILMAZ, YUSUF (SPRINGER-VERLAG ITALIA SRL, 2020)
Background/aim Simple noninvasive fibrosis scores based on routine blood tests have been increasingly investigated as screening tools in different clinical settings. Here, we sought to examine whether the Fibrosis-4 Index (FIB-4) and the non-alcoholic fatty liver disease (NAFLD) fibrosis score (NFS) could perform differently in diabetic versus non-diabetic patients with biopsy-proven NAFLD. Methods We examined 349 patients with biopsy-proven NAFLD (166 with type 2 diabetes and 183 without). Patients with FIB-4 scores < 1.3 and > 2.67 or NFS scores < - 1.455 and > 0.676 were considered at low and high risk of advanced fibrosis, respectively. Results A FIB-4 cutoff value of 1.3-which denotes a low risk of advanced fibrosis-had a specificity of 67% in patients with diabetes and 69% in those without. Conversely, a FIB-4 cutoff value of 2.67-which denotes a high risk of advanced fibrosis-had a sensitivity of 22% in patients with diabetes and 0% in those without. NFS performed similar to FIB-4. Conclusion Both FIB-4 and NFS scores have an acceptable clinical utility in the exclusion of advanced fibrosis in patients with NAFLD, regardless of the presence of type 2 diabetes. However, their usefulness in identifying advanced fibrosis is limited-especially in the absence of diabetes.
Keywords: Non-alcoholic fatty liver disease; Fibrosis scores; Advanced fibrosis; Type 2 diabetes mellitus; Screening; SCORING SYSTEM; NAFLD; DIAGNOSIS